Modelling antibody dynamics in humans after different Ad26.COV2.S vaccination schemes - Dari, Anna; Pérez Ruixo, Juan José; Le Gars, Mathieu; Struyf, Frank; Jacqmin, Philippe (British journal of clinical pharmacology, 2025)
Aims To develop a semimechanistic model that describes the kinetic profile and variability of antibody (Ab) concentrations following vaccination with Ad26.COV2.S at different doses and dosing intervals. Methods Data were collected from participants randomized into 5 clinical trials receiving the Ad26.COV2.S vaccine. The model considered key elements of humoral immune response, dose proportionality and the evolutionary processes of the immune response. Interindividual variability and covariates were explored. Results Fast and slow kinetic phases of Ab and their evolution over time were differentiated. After first and second administrations, Ab concentrations of both phases increased less than dose proportionally, indicating a saturation of B‐cell production processes. Ab concentrations produced during the fast kinetic phase increased significantly after the second administration, indicating an underlying evolutive process after antigen exposures. For the slow kinetic phase, a less pronounced increase occurred after the second and third administrations but was relatively higher in subjects who had low concentrations after the first administration. Ab concentrations of the slow phase were higher in females and decreased with age. After multiple administrations, the fast phase had Ab maximum concentrations about 5 times higher than the slow phase. The limiting kinetic factors in the fast and slow phases were the elimination rates of Ab itself and Ab producing cells, respectively. Conclusion The model appears suitable to quantitatively describe the inter‐ and intraindividual kinetics of the immune response and the impact of covariates after multiple administrations of a vaccine.